Legislasi hukum Islam dalam perspektif produk perundang-undangan di Indonesia: integrasi antara maqasid al-shari'ah dengan tujuan legislasi - Mudzakir Mudzakir (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
The challenge in the implementation of Islamic laws faced by Indonesian Muslims has not to do with the struggle for recognition by national laws. Instead, it deals with effort to clarify their position among various social groups. It also examines how much Islamic laws contribute values that stimulate development, order, peace and welfare for the nation and country. Historically, qur’anic verses in concerning with legal were revealed mostly after the Messenger migrated to Medina, while Meccan verses are identified as to consolidate the ummah so that they were ready to bear the burden imposed by the Islamic laws (taklif). The regulations reflecting shar laws issued by the local governments and their implementation tend to be euphoric taking the chance given by the reform. They have not reflected different social groups on which the regulations will be imposed. Islamic laws as the basic consideration in formulating the local government regulations seem not to have accommodated religious elements comprehensively, i.e. integrating aqidah, akhlaq and shariah guiding people’s behavior conceptually as well as in practice. Therefore, partial implementation of Islamic shariah will result in pseudo-religiousity, and tend to become a problem for the ummah themselves.